An analysis of the impact of tax changes between 1996 and 2012 on the tax burden of individuals in South Africa - Krug, Lee (Rhodes University, Faculty of Commerce, Department of Accounting, 2012)
The objective of the research was to determine whether the changes made to the Income Tax Act, 58 of 1962 between 1996 and 2012, in respect of fringe benefits, allowances, deductions, tax tables and rebates, where these changes apply to individuals, have resulted in relieving the tax burden placed on individuals in South Africa. The research was conducted by means of a critical analysis of documentary data with specific reference to the Income Tax Act, annual amendments to the Income Tax Act, statistics relating to tax collections, the National Budget and the Annual Budget Speeches as tabled by the Minister of Finance. These sources were utilised to analyse the amendments to the Act that have taken place over the last sixteen years, where they impact on the tax liability of an individual. A hypothetical example incorporating all the variables identified in the analysis of the tax amendments was used to provide a detailed analysis of the tax payable by an individual on an inflation-adjusted year-on-year basis. The research found that, whilst personal income tax is still the largest contributor to the national budget of South Africa, its contribution has decreased from 40.2 percent in 1996 to 34.3 percent in 2010. This decrease is partly attributable to the extensive tax reforms undertaken by Government with respect to the tax tables, resulting in a reduction in the marginal tax rates and increased tax rebates which had the effect that the individual taxpayer (as illustrated in the hypothetical example) experienced a decrease in the average rate of tax. In contrast to this, the increase in the taxable income of the hypothetical taxpayer exceeded the average rate of inflation over the period. Furthermore, the actual revenue collected by the government from personal income tax has increased by approximately eleven percent per annum, which far exceeds the average inflation rate of 6.23 percent. The research indicated that this could be the result of the increase in the taxable value of fringe benefits, specifically medical aid contributions and company cars, as well as the inclusion of the full amount of allowances in taxable income and the limits placed on the deductions an individual may claim. The result is a broadening of the tax base of the individual taxpayer. Therefore, although the government may have achieved its goal of a fairer tax system, the amendments made to fringe benefits, allowances and deductions have resulted in an increase in the average taxable income of individuals.
Keywords: Uncatalogued